2017
DOI: 10.1371/journal.pone.0176432
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein protects rat insulinoma INS-1 cells from palmitate-induced lipotoxicity by inducing HO-1

Abstract: Objectiveβ-Cell dysfunction plays a central role in the pathogenesis of type 2 diabetes (T2D), and the identification of novel approaches to improve β-cell function is essential to treat this disease. Baicalein, a flavonoid originally isolated from the root of Scutellaria Baicalensis, has been shown to have beneficial effects on β-cell function. Here, the authors investigated the molecular mechanism responsible for the protective effects of baicalein against palmitate (PA)-induced impaired β-cell function, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The neuroprotective effects could be attributed to NF-κB inhibition and nuclear factor E2-related factor 2/heme oxygenase - 1 (Nrf-2/HO-1) activation (Sandireddy et al, 2016 ). In another study, Kwak et al ( 2017 ) revealed that baicalein, a flavonoid found in traditional Chinese herbal medicine can inhibit the oxidative-nitrosative stress and p38 MAPK activation and subsequently lead to alleviation of diabetic peripheral neuropathy.…”
Section: Role Of Antioxidants In the Prevention Of Age-related Diseasmentioning
confidence: 99%
“…The neuroprotective effects could be attributed to NF-κB inhibition and nuclear factor E2-related factor 2/heme oxygenase - 1 (Nrf-2/HO-1) activation (Sandireddy et al, 2016 ). In another study, Kwak et al ( 2017 ) revealed that baicalein, a flavonoid found in traditional Chinese herbal medicine can inhibit the oxidative-nitrosative stress and p38 MAPK activation and subsequently lead to alleviation of diabetic peripheral neuropathy.…”
Section: Role Of Antioxidants In the Prevention Of Age-related Diseasmentioning
confidence: 99%
“…Though ERK is classically known as an important regulator of cell proliferation, differentiation, and survival (51,52), its role in islet β-cell survival and function still remains controversial. Nonetheless, our previous studies (17,47), as well as other reports (53,54) suggest that the activation of the ERK pathway has a pro-survival role at least for islet β-cells in resisting gluco-or lipo-toxicity. As for the transcriptional regulation of the ERK pathway on PDX1, it is still unclear whether PDX1 is a direct downstream target gene of the ERK pathway or not.…”
Section: Discussionmentioning
confidence: 68%
“…For example, loss of PDX1 results in decreased expression of sarco/endoplasmic reticulum Ca(2+) pumps (SERCA2b), and in turn, leads to a reduction in ER Ca 2+ concentration and subsequent induction of ER stress (59). Besides, previous studies have suggested that ERK activation is involved in apelin, caveolin-1 deficiency or baicalein mediated alleviation of diabetesassociated ER stress and protection of pancreatic βcell against apoptosis (53,54,60). Based on these reports, we believe that TG partially elicits its protective effect on islet β-cells by preventing diabetes-related ER stress, which is also associated with ERK activation and subsequent improvement of PDX1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to TM and TG are known to induce ER stress. To examine the similarity between glucolipotoxicity and other ER stress inducers, the mRNA and protein levels of ER stress markers, Bip/GRP78 and CHOP were analyzed [ 9 ]. After exposed to TM, TG, and HG plus PA, Bip/GRP78 mRNA levels were significantly increased by 4.92 folds, 6.96 folds and 6.14 folds respectively ( Fig 6A , P <0.01).…”
Section: Resultsmentioning
confidence: 99%